Evaluasi Penggunaan Obat Antihipertensi Pada Pasien Hipertensi Dewasa Di Klinik Pelayanan Kesehatan Masyarakat (KPKM) Buaran UIN Syarif Hidayatullah Jakarta - Anis Dwi Kristiyowati (STIKes Kharisma Persada, 2020)
Hypertension is one the diseases with various medical condition. The objective of this research was to find out the rationality of the used of anti hypertension on adult patient with hypertension at Public Health Service Clinic , Buaran, Syarif Hidayatullah, Jakarta in 2018. This research used descriptive design by collected data retrospectively. Data used in this research was medical record sheet of adult patient with hypertension at Public Health Service Clinic, Buaran UIN Syarif Hidayatullah, Jakarta, 2018 with cross-sectional approach. Based on the research, was found that the use of anti hypertension that individual therapy were mostly used as many as 149 patients (66,52%), medicine group that were mostly taken CCB(Amlodipin) as many as 72 patients (32,10%), and group of combined medicine, mostly used were ACE-i+Thiazide(Captopril+HCT) as many as 20 patients (8,9%). Evaluation of absorption of rational medicine on their own criteria, they were precised indication 100%, precised medicine 70,5%, precised patients 100%, precised doses 96,87%. Rationality of absorption of hypertension medicine, the most prescription rational were 151 prescriptions (67,41%).